Pemotongan Gaji Pegawai Swasta untuk Penerapan Tabungan Perumahan Rakyat: Kajian Fiqh Siyasah - Salsabila, Adelia; Burlian, Paisol; Is, Muhamad Sadi (Journal of Judicial Review, 2025)
This study examines the legal challenges arising from the enforcement of Government Regulation No. 21 of 2024 on the Public Housing Savings (Tapera) in Indonesia, which mandates a 3% salary deduction from private sector employees, sparking significant public concern over legal certainty, utility, and fairness. The primary objective of this research is to assess the urgency of Tapera’s implementation and to analyze its alignment with Islamic law (fiqh siyasah), focusing on the principles of maslahah (public interest) and justice within state policy. This study adopts a normative legal research method using a statutory and conceptual approach, focusing on the inventory and analysis of positive law and legal doctrines relevant to Tapera’s framework. Findings indicate that the regulation fails to fully meet the principles of legal certainty, utility, and justice, as reflected in inadequate public consultation and insufficient clarity regarding the distribution and management of collected funds. From the perspective of fiqh siyasah, the enforced salary deductions without clear and fair mechanisms contradict the principles of equitable treatment and voluntary consent emphasized in Islamic law, highlighting concerns of unjust burden on employees. The study also underscores that, despite Tapera’s intended aim to facilitate equitable access to housing for low- and middle-income groups, its current implementation may undermine the welfare state principles envisioned by the Indonesian Constitution and the values of social justice upheld in Islamic governance. Thus, this research emphasizes the need for transparent communication, inclusive policy-making, and restructuring of Tapera’s implementation to ensure it becomes a fair, lawful, and socially beneficial instrument in addressing Indonesia’s housing challenges.